THE TEACHERS' CLINIC. - Garner, S. Paul; Jepsen, Victor (The Accounting Review, 1948)
Not long ago the author's college chose for a first year accounting textbook one of those modern versions whose publishers make life easier for the busy teacher by providing standardized objective type tests at no extra cost. Faced with one of the busiest years in history and with graders or readers obtainable only at premium, it is needless to add that all instructors used the tests. Nevertheless, some of the older teachers used them with a sense of misgiving. In probably no field is the belief more ingrained, both in student and faculty, that the objective test and the problem test differ in their measurement of a student's accounting ability. The latter test, it is believed, really measures true accounting ability while the former may merely measure general intelligence, familiarity with English, etc. Many teachers, therefore, rely exclusively on problem tests for measuring purposes, although they are willing occasionally to use the objective test for study motivation purposes. The reliability and validity of each question needs to be determined by statistical methods rather than psychical ones, and there are many pitfalls for those who attempt haphazardly to construct a reliable objective type test. Publishers spend a great deal of time and money in the development of their tests, and even in these many questions prove to be so ambiguously worded as to impair their value as a measuring device. However, whereas this is true of only a comparatively few questions in the printed forms, it may be true of the majority in a privately developed test, which accordingly may or may not be a reliable measuring instrument.